Comparison of the efficacy and safety of Landiolol and Esmolol in critically ill patients: a propensity score-matched study - Xiang Si; Hao Yuan; Rui Shi; Wenliang Song; Jiayan Guo; Jinlong Jiang; Tao Yang; Xiaoxun Ma; Huiming Wang; Minying Chen; Jianfeng Wu; Xiangdong Guan; et al. (Annals of Intensive Care)
Abstract Background Excessive tachycardia is associated with impaired hemodynamics and worse outcome in critically ill patients. Previous studies suggested beneficial effect of β-blockers administration in ICU patients, including those with septic shock. However, comparisons in ICU settings are lacking. Our study aims to compare Landiolol and Esmolol regarding heart rate control and hemodynamic variables in general ICU patients. Methods This retrospective, observational study was conducted in a 56-bed ICU at a university hospital. A propensity score matching (PSM) was employed to balance baseline differences. Generalized estimating equations (GEE) were used to compare heart rate between two drugs. The primary outcome was heart rate control, while secondary outcomes included hemodynamic response, hospital length of stay (HLOS) and ICU length of stay (ICULOS). Results From June 2016 to December 2022, 438 patients were included after PSM, (292 in the Esmolol group and 146 the in Landiolol group). Baseline heart rate was similar between groups (Landiolol:120.0 [110.2, 131.0] bpm vs. Esmolol:120.0 [111.0, 129.0] bpm, p = 0.925). During 72 h. of β-blocker infusion, Landiolol reduced heart rate by 4.7 (1.3, 8.1) bpm, more than Esmolol (p = 0.007), while preserving a comparable proportion of patients able to stabilize vasopressor doses within the first 24 h. (82.9 vs. 80.8%, respectively, p = 0.596). Norepinephrine doses and lactate levels were similar between groups over 72 h., while the Landiolol group exhibited notably higher minimal ScvO2 levels (72% [63%, 78%] vs 68% [55%, 73%], respectively, p = 0.006) and a lower maximal PCO2 gap compared to the Esmolol group (7.0 [6.0, 9.0] vs. 8.0 [6.0, 10.0] mmHg, respectively, p = 0.040). Patients in the Landiolol group were observed to experience shorter HLOS than patients in the Esmolol group (26.5 [13.0, 42.0] vs 30.0 [17.0, 47.2] days, respectively, p = 0.044) and ICULOS (4.9 [2.8, 10.0] vs.6.7 [3.4, 13.1] days, respectively, p = 0.011). Conclusion Landiolol provides superior heart rate control in critically ill patients with tachycardia compared to Esmolol, without increasing vasopressor requirements during the first 24 h. Findings from ScvO2 levels and PCO2 gap suggest that Landiolol may exert less impact on cardiac output than Esmolol. Further studies, incorporating comprehensive hemodynamic monitoring, are warranted to clarify the clinical implications of heart rate control with β-blockers in ICU patients with tachycardia.